2014
DOI: 10.1111/jpy.12196
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of soil cyanobacteria in the hyper‐arid Atacama Desert, Chile

Abstract: The cyanobacterial diversity of soils of the Atacama Desert (Chile) was investigated using 16S rRNA gene cloning/sequencing directly from soil samples and 16S rRNA gene sequencing from unialgal cultures. Within the hyper-arid Atacama Desert, one of the driest parts of the world, 10 sites with differing altitude and distance to the shore were sampled along a total air-line distance (from south to north) of ~1,100 km. Filamentous cyanobacteria belonging to Nostocophycideae and Synechococcophycideae were present.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 77 publications
(122 reference statements)
2
53
1
1
Order By: Relevance
“…Garcia-Pichel et al (2013) subsequently characterized the ecophysiological divide between these two taxa, and indicated that the distribution of M. vaginatus may be deleteriously affected by anthropogenic global warming. However, M. steenstrupii is almost surely a cluster of several species outside of Microcoleus sensu stricto (Boyer et al 2002), and recent work has shown that representatives identified as M. steentrupii belong to several genera (Mühlsteinova´et al 2014a;Patzelt et al 2014). The biogeographical implications of GarciaPichel et al (2013) are considerably different when one realizes that conclusions about M. steenstrupii really apply to a family (Phormidiaceae) rather than to a single species.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Garcia-Pichel et al (2013) subsequently characterized the ecophysiological divide between these two taxa, and indicated that the distribution of M. vaginatus may be deleteriously affected by anthropogenic global warming. However, M. steenstrupii is almost surely a cluster of several species outside of Microcoleus sensu stricto (Boyer et al 2002), and recent work has shown that representatives identified as M. steentrupii belong to several genera (Mühlsteinova´et al 2014a;Patzelt et al 2014). The biogeographical implications of GarciaPichel et al (2013) are considerably different when one realizes that conclusions about M. steenstrupii really apply to a family (Phormidiaceae) rather than to a single species.…”
Section: Introductionmentioning
confidence: 89%
“…We found Symplocastrum at five sites in the western United States on the basis of enrichment culturing techniques as well as at one site in the Atacama Desert, Chile using clone libraries from environmental samples (Table 1) (Patzelt et al 2014). Strains and clones were assigned codes containing a two-to four-letter code for the sample region and a numerical code representing a specific sampling site within this region (Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies suggest that cyanobacteria are important in the early stages of primary succession processes in soils (Starks et al, 1981;Lukešová, 1993), especially because many species are N 2 fixers, aid in stabilizing soils against erosion, or facilitate production of organic matter in new soils (Bailey et al, 1973;Jürgensen, 1973;Evans and Johansen, 1999;Kubečková et al, 2003;Řeháková et al, 2007). Studies on desert soils has been a particular focus in recent years by several authors (Johansen et al, 1981(Johansen et al, , 1984Ashley et al, 1985;Flechtner et al, 1998Flechtner et al, , 2002Flechtner et al, , 2008Řeháková et al, 2007;Mühlsteinová et al, 2014a,b;Osorio-Santos et al, 2014;Patzelt et al, 2014;Pietrasiak et al, 2014). More recent data suggest that cyanobacterial abundance and productivity can also be substantial in agricultural and forest soils (Hunt et al, 1979;Shimmel and Darley, 1985).…”
Section: A Soils and Arid Environmentsmentioning
confidence: 99%
“…Understandably, newer microfloristic studies tend to focus on previously unexplored localities and habitats (e.g., table mountains, desert and other soils - Kaštovský et al 2011;Patzelt et al 2014;Sherwood et al 2015, respectively). However, when historically surveyed regions are revisited or new localities are added, new records are often found, further demonstrating that our knowledge still needs much improvement (e.g., Johansen et al 2007;Fučíková et al 2015).…”
Section: Introductionmentioning
confidence: 99%